Farm households' perception about sugarcane outgrowers' scheme: Empirical evidence around Wonji/Shoa Sugar Factory - Gutema Bati Fedi; Fekadu Dereje Asefa; Abebe Tafa Waktole (Cogent Economics & Finance, 2022)
The study assessed the perception of contract farm households about sugarcane outgrowers' scheme around the Wonji/Shoa sugar factory. The study utilized primary data collected from randomly selected samples of 200 members of sugarcane-producing farmers' cooperatives through a structured survey questionnaire. Purposively selected ten KIIs and six FGDs were also conducted with contract farmers and stakeholders. The five-point Likert scale measurement was created and applied to measure the perception of respondents about the scheme on considered 26 attributes and analyzed through descriptive statistics. Results revealed that the overall perception of the respondent contract farm households about the scheme was unfavorable with a weighted mean/index score of '2.32 with a mixed perception index score on considered 26 attributes. The study discussed the policy implications of the findings. The main areas of concern are the payment system, the relationship of contract farmers with representatives (from the union, factory, and cooperatives), the income of contract farm households, the provision of services package (like free training, extension services, technical advice), the transparent and comprehensive contract terms and conditions, the provision of basic inputs and production services as per agreement (like adequate land preparation, infield irrigation), the effective and efficient legal framework system, additional support by third parties (on pre and post-harvest, production input provision, basic skill training, and etc.), and both parties should develop trust by having confidence on each other and not by acting opportunistically.
Keywords: 330; perception; sugarcane outgrowers scheme; contract farming; Wonji/Shoa; Oromia; Ethiopia